Web-Based E-Budgeting Design: Case Study at Unwaha Jombang - Budi, Angga Setiya; Anam, Chairul; Sifaunajah, Agus (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Every year, the faculties and units at KH. A. Wahab Hasbullah University submit budget proposals to the Planning Department. Some common issues include low budget absorption and suboptimal reporting. Reporting also faces difficulties as everything is done manually. In an effort to address the aforementioned problems, a system needs to be developed to facilitate communication and coordination among various parties in budget creation, ensuring the formulation of a realistic and achievable budget. Thus, the E-Budgeting system is established to tackle these budget submission challenges. The research methodology involves several stages, including data collection methods (literature review, field study) and system development methods (design phase, coding phase, and testing phase). The goal of this research is to design a budget submission and preparation system at KH. A. Wahab Hasbullah University in Tambakberas Jombang that can expedite the budget disbursement process. The final outcome of this research is the creation of a web-based E-BUDGETING application providing budget processing information accessible to the academic community at KH. A. Wahab Hasbullah University.